Interactions between climate change mitigation, damages, and adaptation: An intertemporal Computable General Equilibrium analysis for Ireland - Kelly C. De Bruin; Clement Kweku Kyei; Loïc Henry; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2024)
This study uses a Computable General Equilibrium (CGE) model to analyse how mitigation and adaptation strategies affect climate change impacts in Ireland. Five impacts-coastal flooding, riverine flooding, heat on labour productivity, human health, and agricultural productivity-are incorporated, along with adaptation costs and benefits for riverine and coastal flooding. Impacts are modelled through increased capital depreciation, reduced labour productivity, healthcare costs, and agricultural productivity shocks. Adaptation involves spending on coastal protection infrastructure through construction. Results indicate that adaptation can cut net climate costs by over half. Secondary general equilibrium impacts and adaptation costs overshadow initial impacts adaptation costs. GDP losses are highest without adaptation (2.6% by 2030), compared to 1.3% with mitigation and 0.6% with optimal adaptation. The study highlights the need for further research on broader impacts and adaptation strategies, emphasizing the importance of considering secondary impacts in policy assessments.
Keywords: 330; Climate change; adaptation; macroeconomy; impact assessment; CGE modelling; Ireland